ANALISIS KETERSEDIAAN RUANG TERBUKA HIJAU KELURAHAN KAYU PUTIH, KECAMATAN OEBOBO, KOTA KUPANG - Manu, Asnat Enggelina; Wulakada, Hamza Huri; rahmawati, arfita (Universitas Nusa Cendana, 2024)
Kayu Putih Village has a large population, namely 54,726 people. As the population increases, the land needed to build houses will also increase. so that green open spaces are neglected. In the Ministerial Decree of the Ministry of Agrarian Affairs and Spatial Planning/National Defense Agency Number 14 of 2022, it is stated that 30% is allocated for green open space, of which 20% is public open space and 10% is private green open space. The objectives of this research: (1) determine the availability of green open space (RTH); (2) knowing the suitability of Green Open Space. This research uses quantitative descriptive research and uses remote sensing techniques and geographic information systems using data collection techniques, namely image interpretation, observation, literature study, documentation. Data analysis techniques include geometric correction, image interpretation, field surveys and analysis of green open space availability based on area area. The results of this research show that the distribution of public green open space is still very minimal. The distribution of green open space (RTH) in Kayu Putih Village shows varying areas. Area of Green Open Space for each Public RTH and Private RTH Areas. The area of green open space based on the area in Kayu Putih Village is 525 hectares, with a composition of public green open space of 356 hectares and private green open space of 175 hectares. Advice for the public to maintain cleanliness.